DISCRIMINATION ON THE BASIS OF GENDER ORIENTATION IN EMPLOYMENT RELATIONS - Dyban, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to carry out an analysis of the problems of legal regulation of combating discrimination on the basis of sexual orientation, taking into account theoretical and practical aspects; to analyze the norms of the Laws of Ukraine: "On the principles of preventing and countering discrimination in Ukraine", "On ensuring equal rights and opportunities for women and men", "On introducing amendments to the Code of Labor Laws of Ukraine on harmonizing legislation in the field of preventing and countering discrimination with the law of the European Union" regarding the legal definition of the concept of "sexual orientation" at the level of the law; to carry out a legal analysis of the compliance of the labor legislation of Ukraine with the basic values defined by the European Social Charter (revised) in the edition of 09.07.2016, as well as the content of the Recommendations of the International Labor Organization on the issue of discrimination in the field of work and occupation No. 111 of 06.25.1958. Research methods: general scientific and special methods were used to achieve the goal of the scientific work. Results: it is claimed that the national legislation of Ukraine on labor requires the implementation of democratic norms of European society with the need for additional regulation of certain issues of countering manifestations of discrimination in labor relations. Problematic issues of national labor legislation regarding the prevention of discrimination based on sexual orientation are highlighted, appropriate conclusions are drawn and solutions are proposed. Discussion: the issue of the spread of discrimination based on sexual orientation in labor relations is raised.